Size-Resolved Electron Solvation in Neutral Water Clusters - Ban, Loren (J Phys Chem A, 2021)
[Image: see text] Cluster-size-resolved ultrafast dynamics of the solvated electron in neutral water clusters with n = 3 to ∼200 molecules are studied with pump–probe time-of-flight mass spectrometry after below band gap excitation. For the smallest clusters, no longer-lived (>100–200 fs) hydrated electrons were detected, indicating a minimum size of n ∼ 14 for being able to sustain hydrated electrons. Larger clusters show a systematic increase of the number of hydrated electrons per molecule on the femtosecond to picosecond time scale. We propose that with increasing cluster size the underlying dynamics is governed by more effective electron formation processes combined with less effective electron loss processes, such as ultrafast hydrogen ejection and recombination. It appears unlikely that any size dependence of the solvent relaxation dynamics would be reflected in the observed time-resolved ion yields.